Ransom ware Attacks on Financial Institutions: A Review of the Literature on Cybersecurity Risks and Countermeasures - Abid, Noman (Information Technology and Science (ITScience), 2023)
Ransom ware threats have become a new and real threat to financial institutions because they present risks to data integrity, business continuity and consumers’ trust. The current review focuses on the evolution of Ransom ware, such as double and triple extortion, Ransom ware as a service, attacks on the cloud services and targeted financial institutions. Banks therefore are experiencing additional pressures as cyber criminals morph their tactics to target weaknesses in both original legacy and new-age or remote work structures and artificial intelligence. To counter these, the most effective approach involves a number of tiered defense inclusions that includes back up of the data, network separation, and patching and general employee education. Threat monitoring especially at an early stage as well as a solid endpoint security solution is necessary, in addition to a clear-cut Incident Response Plan so as to contain the attack consequences. As far as Ransom ware is concerned more focus should be placed on the latest trends and financial institutions should not stick to traditional threats and should embrace new technologies and advanced disaster recovery solutions. Through exercising a proactive approach towards cybersecurity assessment, financial institutions can build up their defenses to protect their significant assets against growing cybersecurity threats, and maintain operational continuity to run a business.